Effective HR communication a framework for communicating HR programmes with IMPACT - Corey, Debra (Kogan Page Limited, 2016)
In today's competitive environment where we are doing everything we can to compete for talent, effective communication ensures we are showcasing our HR programmes in a way which will help us attract, retain and engage talent. Whether introducing new HR programmes or re-launching existing ones, communications help us deliver the key messages so that employees understand, appreciate and action them to meet our HR and business objectives. Effective HR Communication is a practical guide to develop and deliver effective communication campaigns, ensuring that teams have the knowledge, skills and tools to achieve the desired objectives. Effective HR Communication introduces a six-step 'IMPACT' model to explain and demonstrate the critical steps to be followed when developing a communications campaign. This includes steps such as understanding the communication needs and requirements of employees, developing the most robust objectives, selecting and developing the appropriate medium, planning a campaign in an effective manner, leveraging the support of business partners, developing effective communications content, and measuring the success of the campaign. Using a combination of theory, examples, tips and tools from leading experts, this book provides practical information which can easily be used to create effective and impactful communications. Case studies from leading organisations such as BT, LV=, Merlin Entertainments and Reward Gateway are included to further illustrate how communication has been done effectively.